Analisis Integrasi Vertikal Pasar Beras di Indonesia - Asih Kusumaningsih (BBM (Buletin Bisnis & Manajemen), 2015)
Aim for this research consists of (1) knowing trend of rice retail price in Indonesia and unhulled rice price at farm level in Indonesia and (2) identifying vertical integration of rice market in Indonesia. Research method to analyze trend of price is least square method with use annual data from period 2000-2014. Vertical integration of rice market in Indonesia is analyzed with Engle-Granger cointegration model and ECM with use monthly data of retail price in Indonesia and GKP price from period 2008-2014. Result of trend analysis shows that two kind of rice price have increased trend. Analysis of vertical integration of rice market in Indonesia shows that rice market in Indonesia has long term equilibrium relationship and short term equilibrium relationship.Keywords: price, rice, integration, vertical